Algunas consideraciones teóricas de la asistencia social alimentaria y de la evaluación de programas (2010)
ABSTRACT: Around world there is a 1.020 million of people suffering chronic hunger or undernourished, of which 1002 million are currently living in developing countries. As a result of nutritional insecurity, people living this situation could present low academic performance, learning difficulties, growth retardation and malnutrition; they have severe morbidity, high mortality and greater vulnerability to natural disasters, all these factors can be finally translated to poverty. In order to address these consequences, food assistance programs are developed in programs to struggle poverty; these programs have been widespread in Latin America. In Colombia food assistance programs emerge under the concept of social risk management and its actions are lead by the Social Protection System. Regardless of the experience of these institutions developing, following and evaluating the programs; there is still necessary to improve these facts in order to establish public policies based on scientific evidence.